KORELASI ASPEK STATUS EKONOMI DAN PEMBERIAN ASI TERHADAP KEJADIAN STUNTING - Aprilian Lestaluhu, Santi; Mahmud, Mahmud; Chania Arefti, Vyola; Malawat, Ratna; Ayu Wulandari, Ikrawanty (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Stunting is the result of chronic malnutrition that occurs in the first 1000 days of a child's life. The results of a preliminary survey conducted in the period January - December 2022, found 68 cases of stunting at the Umbansari Health Center. The results of interviews during visits to the Puskesmas obtained dat that 8 out of 10 mothers who brought toddlers said they did not provide exclusive breastfeeding due to work factors, and family economy. This study is an observational analytic quantitative study with a cross sectional design. The sampling technique was purposive sampling. Data collection tools using a research questionnaire. Data analysis was performed univariately and bivariately using the SPSS program. The results showed that there was a relationship between economic status (p value 0.002) and breastfeeding (p value 0.045) on the incidence of stunting. It is recommended to the Umbansari Health Center to increase IEC efforts, especially regarding the importance of exclusive breastfeeding for the development of toddlers. Keywords: Toddlers, Economic Status, Stunting